2014
DOI: 10.1371/journal.pone.0104485
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcoding of Bemisia tabaci Complex (Hemiptera: Aleyrodidae) Reveals Southerly Expansion of the Dominant Whitefly Species on Cotton in Pakistan

Abstract: BackgroundAlthough whiteflies (Bemisia tabaci complex) are an important pest of cotton in Pakistan, its taxonomic diversity is poorly understood. As DNA barcoding is an effective tool for resolving species complexes and analyzing species distributions, we used this approach to analyze genetic diversity in the B. tabaci complex and map the distribution of B. tabaci lineages in cotton growing areas of Pakistan.Methods/Principal FindingsSequence diversity in the DNA barcode region (mtCOI-5′) was examined in 593 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 78 publications
4
52
0
1
Order By: Relevance
“…This may be further explained by the minimal to no use of pesticides in the urban areas, which leaves the natural enemies relatively undisturbed, compared to agricultural areas where pesticide use during the cotton‐growing season is frequent to control the whitefly vector, with the caveat that its frequent use often leads to increases in whitefly population sizes (Anthony, Brown, Markham, & Ffrenchconstant, ; Bedford et al, ; Denholm, Cahill, Dennehy, & Horowitz, ; Horowitz & Ishaaya, ). This hypothesis is consistent with the observed small available sample sizes of the Asia II‐5 ( n = 3) and II‐7 ( n = 23) mitotypes (herein) and the results of previous studies reporting similarly low frequencies within Pakistan agroecosystems (Ahmed et al, ; Ashfaq et al, ; Masood et al, ; Paredes‐Montero et al, ).…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…This may be further explained by the minimal to no use of pesticides in the urban areas, which leaves the natural enemies relatively undisturbed, compared to agricultural areas where pesticide use during the cotton‐growing season is frequent to control the whitefly vector, with the caveat that its frequent use often leads to increases in whitefly population sizes (Anthony, Brown, Markham, & Ffrenchconstant, ; Bedford et al, ; Denholm, Cahill, Dennehy, & Horowitz, ; Horowitz & Ishaaya, ). This hypothesis is consistent with the observed small available sample sizes of the Asia II‐5 ( n = 3) and II‐7 ( n = 23) mitotypes (herein) and the results of previous studies reporting similarly low frequencies within Pakistan agroecosystems (Ahmed et al, ; Ashfaq et al, ; Masood et al, ; Paredes‐Montero et al, ).…”
Section: Methodssupporting
confidence: 92%
“…Environment‐associated niche adaptation of B. tabaci can be influenced by endosymbiont community composition, which in turn can alter the distribution of different vector mitotype–virus combinations. In Pakistan and India, studies have shown that B. tabaci mitotypes native to Asia that transmit cotton leaf curl disease‐begomoviruses (CLCuD; Bedford et al, ) have undergone geographic expansion and/or contraction, while at the same time the composition of the cotton leaf curl disease complex has been in flux, potentially corresponding to mitotype fluctuations (Ahmed et al, ; Ashfaq et al, ; Paredes‐Montero et al, ). Although many studies have characterized a number of different begomoviral species and strains associated with CLCuD, only a few have considered whitefly vector–endosymbiont relationships and their dynamics in an ecological context.…”
Section: Introductionmentioning
confidence: 99%
“…The use of barcode data to identify species (Rakauskas and Basilova 2013) as opposed to BINs requires the species in question be represented in the barcode reference library (Ekrem et al 2007). Because the barcode reference library now includes records for many agricultural and forestry pests (Ashfaq et al 2014;Foottit et al 2014;Raupach et al 2014), newly encountered specimens of these species can be identified through barcode analysis. As well, the extension of DNA barcoding protocols onto next-generation sequencing (NGS) platforms (Shokralla et al 2014) is enabling metabarcoding studies that permit large-scale assessments of species composition (Taberlet et al 2012), an approach of high importance in monitoring plant pests.…”
Section: Effectiveness Of Dna Barcodes For Arthropod Identificationmentioning
confidence: 99%
“…Such discrepancies complicate the identification of their component taxa with implications for pest regulation and management. For example, the whitefly, Bemisia tabaci, is now known to be a complex of at least 34 species ) that differ in their invasiveness (De Barro and Ahmed 2011), their capacity to transmit plant pathogens (Chowda-Reddy et al 2012), and their regional pest status (Ashfaq et al 2014). Likewise, two pest thrips, Scirtothrips dorsalis and Thrips tabaci, are species complexes whose members vary in their invasiveness and viral-transmission ability (Jacobson et al 2013;Dickey et al 2015).…”
Section: Practical Implications Of Dna Barcodingmentioning
confidence: 99%
“…Previous studies have identified B. tabaci haplotypes and biotypes23 from Pakistan, including the exotic, invasive MEAM I haplotype (also known as the B biotype) that groups in the North Africa-Mediterranean-Middle East (NA-MED-ME) clade (also, Middle East Asia Minor 1) that was present in only Sindh Province, and two endemic cryptic species that group in the Asia 1 and Asia II 1 clades. The Asia 1 cryptic species was identified in Punjab and Sindh Province, whereas, Asia II 1 was present only in Punjab Province242526. In a recent study that analyzed 593 whitefly collections from 255 locations of Pakistan, the presence of the aforementioned two cryptic species, was confirmed, including Asia II-5 from cotton and Asia II-7 from cotton and non-cotton hosts, and an additional previously uncharacterized species was reported from cotton plants, referred to as ‘Pakistan’25.…”
mentioning
confidence: 99%